KESIAPAN PETANI KELAPA SAWIT DALAM MENGHADAPI PEREMAJAAN KEBUN (REPLANTING) DI KAMPUNG DELIMA JAYA KECAMATAN KERINCI KANAN KABUPATEN SIAK - Saputri, Een; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in the village of Delima Jaya districts Kerinci Kanan Siak regency. The purpose of this study is to find out how the readiness of oil palm farmers in facting the rejuvenation of the garden (replanting) in the village of Delima Jaya, to analyze the economic impact of the rejuvenation of oil palm plantations (replanting) in the village of Delima Jaya. The main problem in this study is the age of the oil palm trees that are old and should be in the replanting (replanting) but farmers do not have the capital to rejuvenate the garden. Sampe sampling in the research is by purposive sampling technique. The method used is qualitative method with descriptive approach. The instrument used in the filtering data is observation, documentation, and in-depth interviews. The result of this research is the fruits that have been done by the oil palm farmers in facting the rejuvenation of the garden (replanting) that is to have another garden instead of replanting his garden, the existence of savings, have jobs and other pears. As for the impact that arises is the non-productive period of oil palm crops and farmers income no longer exists.Keywords : Readiness, Replanting, Farmers